2019
DOI: 10.4236/oju.2019.91001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Therapeutic Management of Male Infertility in Thies, Senegal

Abstract: Objective: To evaluate the clinical and therapeutic aspects of male subfertility in the Region of Thies. Patients and methods: This is a retrospective and analytical study involving patients followed for subfertility over a period of 4 years from January 2013 to November 2017 at the level of 3 health structures in the region of Thies. Results: During the period, we collected 201 patients. The average age was 38 ± 8.4 years with a greater distribution in the age group 30-39 years. Primary subfertility was predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…This explains on the one hand the low rate of radical method in our series due to the low socio-economic level of our patients. Fall et al [38] in Dakar as well as Diallo et al [5] in Thies demonstrated the effectiveness of surgical castration which improves the clinical symptoms of patients.…”
Section: Treatmentmentioning
confidence: 99%
“…This explains on the one hand the low rate of radical method in our series due to the low socio-economic level of our patients. Fall et al [38] in Dakar as well as Diallo et al [5] in Thies demonstrated the effectiveness of surgical castration which improves the clinical symptoms of patients.…”
Section: Treatmentmentioning
confidence: 99%